Metronidazole Potentiation by Panax Ginseng and Symphytum officinale: A New Strategy for P. gingivalis Infection Control - Salah M. Ibrahim; Abbas S. Al-Mizraqchi; Julfikar Haider (MDPI AG, 2023)
The important periodontal disease pathogen Porphyromonas gingivalis produces thick biofilms that increase its pathogenicity. Finding natural antimicrobial agents is crucial because of the rise in antibiotic resistance. The purpose of this study was to determine if plant extracts such as Symphytum officinale (S) and Panax Ginseng (G) were effective against P. gingivalis separately and in combination with a common antibiotic, metronidazole (F). Six different dilutions were produced using the plant extracts in different concentrations and antibiotics separately and in combination with F, G, and S using the two-fold serial dilution technique. To evaluate the effects of these substances, biofilm inhibition experiments were conducted. Plaque samples were collected from periodontitis patients to isolate P. gingivalis, and a standard strain of P. gingivalis (ATCC 33277) was purchased. Additionally, Acylated Homoserine Lactones (AHLs) detection was carried out to look for any activity that would interfere with quorum sensing. GraphPad Prism was used for statistical analysis with a p-value < 0.05. The combinations of Symphytum officinale and metronidazole (S+F) showed the maximum effectiveness in biofilm inhibition (98.7%), which was slightly better than G+F (98.2%), with substantial variations in biofilm inhibition levels in different treatment regimes. Notably, the patient isolate was more active than the standard strain. Additionally, the plant extracts and their combinations at particular dilutions had notable inhibitory effects on the generation of AHL (p < 0.05). The study highlights the possibility of Symphytum officinale and Panax Ginseng as effective treatments for P. gingivalis biofilm and AHLs, both on their own and in combination with metronidazole. These organic substances may open the door to cutting-edge methods of treating periodontal disorders.